RENEW OF THE ECONOMIC RESOURCES OF THE ENTERPRISE IN THE INNOVATIVE PROCESS - Городянська, Лариса В. (Journal of Strategic Economic Research, 2024)
The process of production and creation of a supply of new goods and services at the enterprise is based on economic resources that are not inexhaustible and require renewal. Therefore, the purpose of the article is to determine the connections between renewal and innovation, as key factors of the process of renewal and innovation at the enterprise. The results of the research were obtained by using the theoretical analysis of literary sources, the dialectical method of cognition, modeling, decomposition, system analysis and synthesis, theoretical generalizations, grouping, and systematization of data for the formation of current and conclusions. The connections between the renewal of economic resources and innovations as key factors of the processes of renewal and innovation at the enterprise have been established and substantiated. It is argued that the effective renewation of resources contributes to the stimulation of innovations, which in turn affects the ability of the enterprise for sustainable development. The key areas of renewation of the company`s resources in the innovation process have been defined and substantiated. It is noted that innovative development can be based on internal resources and competencies of the enterprise but also requires external partnership with research institutions. It was established that the renewal of economic resources and innovation are interrelated factors that significantly affect the development of the enterprise. An effective balance between them can contribute to maintaining sustainable growth, competitiveness, and stability of the enterprise in the long term. It is proposed to combine renewal, and innovation at the enterprise under a single concept – a renewal and innovation process that combines the preservation of resources with the constant improvement and development of technologies for their use. The obtained results of scientific research on the interaction of renewal of economic resources and innovative processes allow the enterprise to effectively use existing resources to create new values, as well as to adapt to changing market conditions and ensure sustainable development.